Logistic Regression on Physical Activities Analysis Related to Depression in Elderly (International Journal of Nursing Education, 2021)
Background: The risk of depression in the elderly is currently exacerbated by the health situation of theCoronavirus Disease 2019 (COVID-19) pandemic that has reached the entire world, including Indonesia.The imposition of physical distancing and restrictions on activities outside the home will have an impact ondiscomfort for all individuals, including the elderly. The elderly are forced to stay in their respective homesthat causes reduced physical activity. If this condition continues, it can reduce endurance, cause discomfort,boredom, anxiety, and depression in the elderly.Objective: This study aimed to identify the effect of physical activity on of depression in the elderly atIntegrated Health Center (Posyandu), Kasin Sub-District, Working Area of Puskesmas Bareng, Malang City.Methods: This type of analytic correlative research was categorized as a quantitative survey type with crosssectional design. The sample was 54 elderly aged 60 years taken by random sampling. The instruments usedwere the Geriatric Depression Scale for screening depression incidents and the questionnaire for assessingdemographic data and physical activity. Data were analyzed using multivariate logistic regression method.Results: Exercising, doing outwork had a significant effect on the occurrence of depression in the elderly,with a sig value of exercising 0.004 and doing homework at 0.047. exercise can reduce the risk of depressionby 99% and doing homework can reduce the risk of depression by 10%.Conclusion: Elderly should keep doing homework every day and keep in exercising regularly every weekto reduce the risk of depression during the Covid-19 period.
Keywords: Physical activity, depression, elderly.